Amidoximated hydrotalcite material as well as preparation method and application thereof
By modifying hydrotalcite with amidoximetallization, using its layered structure and hydroxy functional groups, a high-affinity amidoxime group is formed, which solves the problem of low uranium ion extraction efficiency in seawater and achieves efficient uranium ion adsorption and identify.
Patent Information
- Application Number
- CN202411661661.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2024-12-31
AI Technical Summary
The prior art is difficult to efficiently extract uranium ions from seawater, especially because the uranium concentration in seawater is low and the presence of a large number of coexisting ions, resulting in insufficient selectivity and efficiency of adsorbent materials.
By performing geminoxime modification on hydrotalcite, the amino and cyano groups are grafted and modified by grafting and modifying the amino and cyano groups with high affinity to form a geminoxime group with high affinity to improve uranium Adsorption properties of acyl ions.
It significantly improves the adsorption performance and selectivity of uranyl ions, achieves efficient identification and adsorption of uranium ions, and is suitable for seawater uranium extraction and spent fuel after-treatment.
Smart Images

Figure CN119215867A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to an amidoximated hydrotalcite material and a preparation method and application thereof, belonging to the technical field of material preparation. Background Art
[0002] The continuous growth of energy demand has led to over-exploitation of resources, resulting in a decrease in non-renewable fossil energy and increasingly severe environmental problems. Nuclear energy, as a sustainable and clean energy source, has become the best choice to solve this problem. Uranium is an important source of energy production in the nuclear industry, but uranium resources on land are quite limited, and the total uranium reserves in seawater are nearly 1,000 times that of land. If the uranium ions in seawater can be effectively separated, then the supply of uranium resources in the future will be guaranteed to a certain extent. In recent years, the use of adsorption materials for the efficient extraction of uranium from seawater has attracted people's attention, but there are still many challenges, such as the low uranium concentration in seawater (3.3ppb), and the presence of a large number of coexisting ions in seawater (such as Na + , K + , Ca 2+ Mg 2+ 、Zn 2+ 、Ni 2+ , Cu 2+ , Pb 2+ Therefore, it is crucial to develop adsorbent materials with excellent performance to selectively separate uranyl ions from seawater in a low-cost and efficient manner.
[0003] Layered double hydroxides (LDHs, also known as hydrotalcites, have a general chemical formula of [M 2+ 1-x M 3+ x (OH - )2] x+ (A n- ) x / n mH2O, where M 2+ is a divalent metal cation, M 3+ is a trivalent metal cation, A n- It is an interlayer anion) and is a clay material with a unique two-dimensional layered structure. It has the advantages of adjustable structure, low cost and easy synthesis. Due to its abundant active sites and large specific surface area, it has been widely used in the field of adsorption. At the same time, hydroxyl functional groups are commonly found on the surface of hydrotalcite. These functional groups are easy to be functionalized, that is, the selective adsorption performance of the material can be improved by grafting adsorption groups that have specific recognition for uranyl ions.
[0004] Amidoxime (-(NH2)C=N-OH, -AO) has a high chelating affinity for uranium and is currently recognized as one of the groups with excellent selectivity for uranium. Amidoxime is usually converted from cyano (-C≡N), including oxime (C=N-OH) and amino (-NH2) on carbon atoms. The oxime nitrogen, oxime oxygen and amino nitrogen in the structure all contain unbonded lone pairs of electrons, which can act as electron donors to coordinate with uranium ions.
[0005] Therefore, the currently advantageous direction is to modify the hydrotalcite by amidoximation to improve the adsorption selectivity and adsorption amount of uranyl ions. Summary of the invention
[0006] In view of the technical problems existing in the prior art, the first object of the present invention is to provide an amidoxime hydrotalcite material, which has a two-dimensional layered structure, a large specific surface area, and is surface-modified with amidoxime modification groups, which can directionally identify or fix uranyl ions in different forms, thereby significantly improving the adsorption performance of uranyl ions.
[0007] The second object of the present invention is to provide a method for preparing an amidoximated hydrotalcite material, which has the advantages of low cost, simple operation and easy scalability.
[0008] The third object of the present invention is to provide an application of an amidoximated hydrotalcite material, which is used as an adsorbent for the adsorption of uranyl ions, and can achieve highly specific recognition and efficient adsorption of uranyl ions. It is expected to be applied in the fields of uranium extraction from seawater, spent fuel post-processing, radionuclide detection, etc.
[0009] In order to achieve the above technical objectives, the present invention provides a method for preparing an amidoximated hydrotalcite material, which comprises the following steps: grafting and modifying an amino group on a hydrotalcite to obtain an amidated modified hydrotalcite material; grafting and modifying an aldehyde group on the amidated modified hydrotalcite material to obtain an aldehyde-modified hydrotalcite material; subjecting the aldehyde-modified hydrotalcite material to a condensation reaction with a reagent containing both an amino group and a cyanide group to obtain a cyanated modified hydrotalcite material; and subjecting the cyanated modified hydrotalcite material to an amidoximation reaction with an oximating reagent to obtain the obtained product.
[0010] In the preparation process of amidoximated hydrotalcite materials, the key step is the amidoximation reaction of cyanated modified hydrotalcite with an oximation reagent, and the experimental conditions (pH, temperature, mass ratio) need to be reasonably controlled to obtain an amidoximated hydrotalcite final product with uniform structure, high degree of oximation and complete hydrotalcite base.
[0011] As a preferred solution, the grafted amino group is modified by an aminosilane coupling agent, including but not limited to 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane (APTES), N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane and N-β-(aminoethyl)-γ-aminopropylmethyldimethoxysilane, the purity of the reagent is experimental grade or above, and APTES is further preferred, and the purity of the reagent is analytical grade. The grafted aldehyde group is modified by a dialdehyde reagent, such as succinaldehyde, glutaraldehyde and adipic acid.
[0012] The reaction mechanism of the preparation process of the present invention is:
[0013] The present invention firstly adds a silane coupling agent having an amino group, and the product generated after hydrolysis is NH2-(CH2)3-Si(OH)3, wherein the Si-OH bond undergoes a dehydration condensation reaction with the hydroxyl group (M-OH, M is a metal cation) on the surface of the hydrotalcite, so that the amino group of the silane coupling agent is grafted on the surface of the hydrotalcite to obtain an amino-modified hydrotalcite material (NH2-LDHs), and the chemical structure of the product is shown in Formula I:
[0014]
[0015] Then, a dialdehyde reagent is used as a cross-linking agent, and the aldehyde group at one end of the dialdehyde reagent is condensed with the primary amine group on the surface of NH2-LDHs, so that the dialdehyde reagent is grafted on the surface of the hydrotalcite material to obtain aldehyde-modified hydrotalcite (CHO-LDHs), and the aldehyde group at the other end is condensed with the primary amine group of the amino- and cyano-containing reagents, and finally the cyano group is grafted on the surface of the hydrotalcite to obtain a cyano-modified hydrotalcite material (CN-LDHs), and the chemical structure of the product is shown in Formula II (taking glutaraldehyde as an example):
[0016]
[0017] Finally, by adding an oximation reagent solution, the cyanide group of the cyanated hydrotalcite material can be promoted to be oximated by amido, and at the same time, a neutralizing agent is added to the solution to adjust the pH value of the solution so that the hydrogen ions are neutralized to avoid affecting the reaction, and finally a fully amidoximate hydrotalcite final product (AO-LDHs) is obtained. The chemical structure of the product is shown in Formula III:
[0018]
[0019] As a preferred solution, the hydrotalcite has the general structural formula [M 2+ 1-x M 3+ x (OH - )2] x+ (An- ) x / n mH2O; where M 2+ With M 3+ The element ratio is (2-5):1; M 2+ Mg 2+ 、Ni 2+ or Zn 2+ ;M 3+ For Al 3+ or Fe 3+ ; A n- For CO3 2- 、NO3 - or C1 - The hydrotalcite has a purity of 96-99.5%, a particle size of 0.3-3 μm, and a shape of flake, rod or sphere. Compared with other types of hydrotalcite, nickel-aluminum hydrotalcite has low preparation cost, is easier to obtain, has high surface adsorption capacity and reaction activity, is conducive to the preparation of composite materials, and enhances the ability of composite materials to enrich uranyl ions. Further preferably, the hydrotalcite is nickel-aluminum hydrotalcite (chemical formula Ni 0.75 Al 0.25 (OH)2(NO3) 0.25 ), purity is 99.5%, particle size is 0.5~1μm, shape is flake, M 2+ With M 3+ The element ratio is 3:1.
[0020] As a preferred solution, the solid-liquid ratio of the hydrotalcite to the aminosilane coupling agent is (0.25-2.5) g: (1-10) mL; the solid-liquid ratio of the hydrotalcite to the aminosilane coupling agent has a direct impact on the effect of the amination modification. If the solid-liquid ratio is too large, the amination reaction of the hydrotalcite hydroxyl group may not be complete, thereby affecting the subsequent modification process; and if the solid-liquid ratio is too small, part of the aminosilane coupling agent may not be able to fully react with the hydrotalcite, resulting in a waste of raw materials. At the same time, removing excess aminosilane coupling agent also increases the complexity of the operation.
[0021] As a preferred solution, the reaction conditions for the graft modification of amino groups are: temperature of 40-100°C, reaction time of 6-24h, and use of at least one of water, ethanol, methanol, acetone, toluene, N,N-dimethylformamide, dimethyl sulfoxide and acetonitrile as solvent. More preferably, the temperature is 60-80°C, the reaction time is 12-24h, and use of at least one of anhydrous ethanol, toluene and N,N-dimethylformamide as solvent.
[0022] As a preferred solution, the solid-liquid ratio of the amino-modified hydrotalcite material to the dialdehyde reagent is (0.5-5) g: (1-20) mL.
[0023] As a preferred solution, the reaction conditions for the graft modification of aldehyde groups are: temperature of 20-100°C, reaction time of 2-12 hours, and use of at least one of water, ethanol, ether, chloroform and glacial acetic acid as solvent. More preferably, the temperature is 25-40°C, the reaction time is 3-6 hours, and anhydrous ethanol and glacial acetic acid are used as solvents.
[0024] As a preferred solution, the reagent containing both amino and cyano groups is diaminomaleonitrile or aminoacetonitrile.
[0025] As a preferred solution, the mass ratio of the aldehyde-modified hydrotalcite material to the reagent containing both amino and cyano groups is (0.1-2):(0.5-4).
[0026] As a preferred solution, the condensation reaction conditions are: temperature of 20-80°C, reaction time of 2-12h, and use of at least one of water, anhydrous ethanol, N,N-dimethylformamide, dimethyl sulfoxide, and N-methylpyrrolidone as solvent. More preferably, the temperature is 25-40°C, the reaction time is 3-6h, and use of at least one of anhydrous ethanol, N,N-dimethylformamide, and N-methylpyrrolidone.
[0027] As a preferred solution, the amidoximation reaction is to dissolve the oximation reagent, adjust the solution pH to 6-8, and then add the cyanation-modified hydrotalcite material; the present invention adjusts the pH value of the solution to neutralize the hydrogen ions to avoid affecting the reaction. The pH is further preferably 6.8-7.2.
[0028] As a preferred solution, the reagent for adjusting pH is at least one of potassium hydroxide, sodium hydroxide and anhydrous sodium carbonate, and is more preferably anhydrous sodium carbonate.
[0029] As a preferred solution, the oximation agent includes at least one of hydroxylamine hydrochloride, hydroxylamine sulfate and hydroxylamine phosphate, and more preferably hydroxylamine hydrochloride.
[0030] As a preferred solution, the mass ratio of the cyanated hydrotalcite material to the oximation agent is (0.1-1): (0.2-2); the mass ratio of the cyanated hydrotalcite material to the oximation agent has a direct impact on the adsorption performance of the amidoximated hydrotalcite material. If the mass ratio is too large, the oximation reaction of the cyanated hydrotalcite may not be complete, thereby reducing the adsorption effect of the material on uranyl ions; and if the mass ratio is too small, it may lead to excessive oximation agent in the reaction, which not only causes a waste of raw materials, but also remains in the product as an impurity, resulting in a decrease in product purity.
[0031] As a preferred scheme, the conditions of the amidoximation reaction are: temperature of 60 to 100° C., time of 6 to 24 h, and at least one of water, ethanol, isopropanol, methanol, acetone, glycerol, acetonitrile and chloroform as solvent; within the temperature and time range of the amidoximation reaction selected by the present invention, while ensuring the reaction yield, an amidoximation hydrotalcite final product with uniform structure, high degree of oximation and complete hydrotalcite base can be obtained. The further preferred temperature is 60 to 80° C., the time is 6 to 12 h, and at least one of water, ethanol and isopropanol is used.
[0032] The present invention also provides an amidoxime hydrotalcite material obtained by the above preparation method. The material has a two-dimensional layered structure, a large specific surface area, and is modified with amidoxime modification groups on the surface, which can directionally identify or fix uranyl ions in different forms, significantly improving the adsorption performance of uranyl ions.
[0033] Finally, the present invention also provides an application of the amidoximated hydrotalcite material, which is used as an adsorbent for adsorption of uranyl ions, and can achieve high-specific recognition and efficient adsorption of uranyl ions.
[0034] The principle that the amidoxime hydrotalcite material of the present invention can realize high-specific recognition and efficient adsorption of uranyl ions is that: hydrotalcite has a large specific surface area and abundant surface hydroxyl groups, providing a large number of grafting sites for the amidoxime groups, and these groups can be evenly distributed on the surface of the hydrotalcite. The amidoxime group has a high affinity for uranyl ions and can form a stable coordination bond with the uranyl ions, thereby realizing high-specific recognition and efficient adsorption of uranyl ions, and a large number of amidoxime groups can form a synergistic effect. When an amidoxime group coordinates with the uranyl ion, the surrounding amidoxime groups can further form a chelation effect to stabilize the adsorption state of the uranyl ion through steric hindrance or charge interaction, thereby enhancing the specific adsorption effect. In addition, hydrotalcite has a unique layered structure, and there are exchangeable anions between the layers. This layered structure provides more space to accommodate uranyl ions, and the large specific surface area allows uranyl ions to have more opportunities to approach the active sites of the amidoxime hydrotalcite material, thereby significantly improving the high-specific recognition and efficient adsorption of uranyl ions.
[0035] As a preferred solution, the adsorption conditions are: pH 3-9, the solid-liquid ratio of amidoxime hydrotalcite material to uranyl ion solution is (3-12) mg: 40 mL. The amidoxime group will be partially hydrolyzed under acidic conditions, so it is not suitable for UO2 2+ When the pH value is too high, U(VI) is mainly adsorbed in the form of UO2(OH)3 - 、UO2(CO3)3 4- and UO2(CO3)2 2-The anionic complex exists, and the amidoxime group is difficult to react with it. The pH is preferably 5 to 7; the solid-liquid ratio is (4 to 6) mg: 40 mL.
[0036] Compared with the prior art, the present invention has the following beneficial effects:
[0037] 1) The present invention firstly uses an aminosilane coupling agent to graft the amino group of hydrotalcite, then uses a crosslinking agent to graft the cyano group on the surface of the hydrotalcite, and finally obtains the amidoximated hydrotalcite powder material by amidoximation of the cyano group. The method has low cost, simple operation and easy scalability.
[0038] 2) The amidoximated hydrotalcite material of the present invention has a two-dimensional layered structure, a large specific surface area, and is surface-modified with amidoxim modification groups, which can directionally identify or fix uranyl ions in different forms, thereby significantly improving the adsorption performance of uranyl ions.
[0039] 3) The amidoxime hydrotalcite material of the present invention provides a large number of uniformly distributed grafting sites for amidoxime groups based on the large specific surface area and abundant surface hydroxyl groups of hydrotalcite, which can form stable coordination bonds with uranyl ions. At the same time, based on the synergistic effect between a large number of amidoxime groups and the unique layered structure of hydrotalcite, the highly specific recognition and efficient adsorption of uranyl ions are significantly improved, and the adsorption effect is best in a neutral environment. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 It is a preparation flow chart of the amidoxime nickel aluminum hydrotalcite of Example 1 of the present invention, wherein LDHs is NiAl-LDHs.
[0041] Figure 2 It is the Fourier transform infrared spectrum (FT-IR) graph of NiAl-LDHs, CHO-NiAl-LDHs obtained in Example 1, CN-NiAl-LDHs, and AO-NiAl-LDHs.
[0042] Figure 3 This is an X-ray photoelectron spectrum (XPS) diagram of the final product AO-NiAl-LDHs obtained in Example 1.
[0043] Figure 4 The results are as follows: the AO-NiAl-LDHs obtained in Example 1 and the unmodified NiAl-LDHs were used to measure the UO2 2+ Adsorption amount diagram.
[0044] Figure 5 The AO-NiAl-LDHs obtained in Example 1 was used to absorb UO2 under different adsorbent quality conditions in simulated seawater solution.2+ Adsorption amount diagram.
[0045] Figure 6 Example 3 is to use the AO-NiAl-LDHs obtained in Example 1 to remove UO2 in the presence of interfering ions in a uranium-containing solution. 2+ Adsorption amount diagram. DETAILED DESCRIPTION
[0046] In order to further illustrate the present invention, the contents of the present invention are described in detail below in conjunction with the examples. However, it should be understood that these examples are implemented on the premise of the technical solution of the present invention, and detailed implementation methods and specific operating processes are given only to further illustrate the features and advantages of the present invention, rather than to limit the claims of the present invention. The protection scope of the present invention is not limited to the following examples.
[0047] The chemical formula of NiAl-LDHs used in the examples and comparative examples of the present invention is Ni 0.75 Al 0.25 (OH)2(NO3) 0.25 , purity is 99.5%, particle size is 0.5-1μm, and the shape is flake.
[0048] Example 1
[0049] 1) Preparation of NH2-NiAl-LDHs
[0050] Weigh 0.5g NiAl-LDHs and 5mL APTES respectively and add them to 50mL anhydrous ethanol, stir at 80°C for 12h, so that the hydroxyl groups on the surface of hydrotalcite react with the hydrolyzed silane coupling agent to undergo dehydration condensation reaction to graft amino groups. The solid product obtained by the reaction is washed three times with anhydrous ethanol and deionized water respectively, the centrifugal speed is 8000rpm / min, the centrifugal time is 10min, and the centrifugal precipitate is dried at 60°C for 12h to obtain NH2-NiAl-LDHs.
[0051] 2) Preparation and characterization of CHO-NiAl-LDHs
[0052] Take 0.5gNH2-NiAl-LDHs and 1mL glutaraldehyde (12%) and add them to 100mL anhydrous ethanol. Stir at room temperature (25°C) for 3h to allow the aldehyde group of glutaraldehyde to undergo condensation reaction with the primary amine group on the surface of NH2-NiAl-LDHs to be grafted onto the surface of hydrotalcite to become a cross-linking agent between NH2-NiAl-LDHs and cyanide reagents. The solid product after the reaction is washed three times by centrifugation with anhydrous ethanol, and the precipitate is dried at 60°C for 12h to obtain CHO-NiAl-LDHs.
[0053] The obtained CHO-NiAl-LDHs were characterized by Fourier transform infrared spectroscopy (FT-IR). Figure 2 As shown in the figure, NiAl-LDHs represents the initial nickel-aluminum hydrotalcite without grafting reaction, and CHO-NiAl-LDHs represents glutaraldehyde grafted on the surface of hydrotalcite as a crosslinking agent. Comparing the two spectra, it can be seen that after the grafting reaction of NiAl-LDHs, its FT-IR spectrum at 1041cm -1 and 1137cm -1 There is an obvious vibration peak belonging to the Si-O-Si bond at 2924 cm -1 and 1680cm -1 The stretching vibration peak at belongs to the aldehyde group, indicating that the aldehyde group at one end of glutaraldehyde undergoes a condensation reaction with the amino end of APTES.
[0054] 3) Preparation and characterization of CN-NiAl-LDHs
[0055] Weigh 0.5 g of CHO-NiAl-LDHs and 0.5 g of diaminomaleonitrile and disperse them in 100 mL of anhydrous ethanol. Stir at room temperature (25°C) for 3 h to allow the aldehyde group of CHO-NiAl-LDHs to undergo a condensation reaction with the primary amine group of diaminomaleonitrile to introduce a cyano group and graft it on the surface of the hydrotalcite. The solid product after the reaction was washed three times by centrifugation with anhydrous ethanol and dried at 60°C for 12 h to obtain CN-NiAl-LDHs.
[0056] FT-IR characterization of CN-NiAl-LDHs was performed, such as Figure 2 As shown in the figure, by comparing the spectra of CHO-NiAl-LDHs and CN-NiAl-LDHs, it can be seen that the FT-IR spectrum of CN-NiAl-LDHs is at 2186 cm -1 There is a vibration peak at 1645cm -1 The vibration peak belonging to the C=N bond at is significantly larger than that of CHO-NiAl-LDHs, confirming that the hydrotalcite has achieved the grafting reaction of the cyano group.
[0057] 4) Preparation and characterization of the final product (AO-NiAl-LDHs)
[0058] Weigh 0.5 g of hydroxylamine hydrochloride and dissolve it in 100 mL of ethanol aqueous solution (V 乙醇 :V 水=9:1), add a certain amount of anhydrous sodium carbonate to adjust the pH value of the solution to 7.0, then add 0.25g CN-NiAl-LDHs, stir and react at 80°C for 6h to make the cyano group completely undergo oximation reaction. The suspension after the reaction is centrifuged and washed several times with anhydrous ethanol and deionized water until the supernatant is neutral, and take the precipitate and place it in a vacuum oven at 60°C to dry for 12h to obtain amidoximated nickel aluminum hydrotalcite powder.
[0059] The samples were characterized by FT-IR. Figure 2 As shown in the spectrum of AO-NiAl-LDHs in the figure, after the oximation reaction of CN-NiAl-LDHs, the vibration peak of the C≡N bond of AO-NiAl-LDHs basically disappeared, and the peak at 1645cm -1 The change of the characteristic peak at 1196cm is due to the effect of the C=N bond and the -1 The characteristic peak at is attributed to the CN bond of the amidoxime group, confirming that sufficient oximation reaction occurred and the final product AO-NiAl-LDHs was generated.
[0060] XPS spectroscopy was used to further analyze the chemical composition and elemental chemical states of the AO-NiAl-LDHs surface. Figure 3 As shown in (a), the photoelectron peaks of Ni 2p, Al 2p, Si 2p, C 1s, O 1s and N1s are all present in the XPS full spectrum of AO-NiAl-LDHs. The XPS fine spectra of C1s, N 1s and O1s core levels of AO-NiAl-LDHs are shown in Figure 2. Figure 3 As shown in (b) to (d). The characteristic peaks of the C1s spectrum at 283.3, 284.7, 286.2 and 288.0 eV binding energies correspond to the excitation of C–N, C–C, C=N and C=O bonds, respectively, indicating that the grafting reaction of aldehyde and cyano groups and the amidoximation reaction occurred during the synthesis process. The N 1s spectrum can be fitted into three peaks, and the characteristic peaks at 397.6, 399.0 and 400.3 eV binding energies represent CN, C=N and NO bonds, respectively. The presence of the NO bond confirms that the composite material contains amidoxime groups. The O 1s spectrum can observe characteristic peaks at 528.6, 530.1, 531.1 and 532.2 eV binding energies, which match the MO, Si-O, M-OH and NO bonds on the sample surface. The NO bond also indicates that the grafting of amidoxime groups has been successfully achieved.
[0061] Example 2
[0062] The only difference between this embodiment and embodiment 1 is that the amount of CN-NiAl-LDHs in step 4) is changed to 0.125 g, and the other conditions and parameters are the same, to obtain AO-NiAl-LDHs-1.
[0063] Example 3
[0064] The only difference between this embodiment and embodiment 1 is that the amount of CN-NiAl-LDHs in step 4) is changed to 0.5 g, and the other conditions and parameters are the same, to obtain AO-NiAl-LDHs-2.
[0065] Application Example 1: UO2 in simulated seawater solution 2+ Adsorption Application
[0066] Weigh 2.1091g of uranyl nitrate hexahydrate (UO2(NO3)2·6H2O) accurately, dissolve it completely with dilute nitric acid solution, transfer it to a 1L volumetric flask, add deionized water to make up to volume, obtain a 1g / L uranium standard solution, and finally dilute it to the concentration required for the adsorption experiment. Weigh 0.55M NaCl into the uranium solution, stir and dissolve, and obtain a simulated seawater solution.
[0067] Batch adsorption experiments were carried out in 100 mL conical flasks under different experimental conditions such as pH, adsorbent dosage and interfering ions. 5 mg of adsorbent was added to a conical flask containing 40 mL of simulated seawater solution, and the pH was adjusted using HNO3 or NaOH solution. The adsorption experiment was carried out using a reciprocating water bath shaker, and the supernatant was taken for detection after the reaction. The concentration of U(VI) in the solution was determined by arsenazo III spectrophotometry. To reduce experimental errors, all experimental data are the average of three repeated experiments.
[0068] Detection method: Use azoarsine III solution as a colorimetric agent, pure NaCl solution as a reference agent, and sodium acetate-chloroacetic acid mixed solution as a buffer solution. Use a pipette to take 0.5 mL of the supernatant and colorimetric agent, and dilute to 5.0 mL with buffer solution. For the blank group, use pure NaCl solution instead of simulated seawater solution. Then use a UV-visible spectrophotometer to detect its absorbance at a wavelength of 652 nm.
[0069] The effects of AO-NiAl-LDHs prepared in Example 1 and unmodified NiAl-LDHs on the degradation of UO2 were investigated under different pH conditions. 2+ The adsorption capacity (experimental conditions: adsorbent mass 5 mg, initial uranium concentration 30 mg·L -1 , pH value is 3-9, the volume of simulated seawater solution is 40 mL, the adsorption time is 12 h, and the reaction temperature is 298 K).
[0070] Figure 4 It shows that when the initial pH value of the solution is 3-6, the adsorbent has a strong affinity for UO2 2+ When the initial pH value of the solution is 6-9, the adsorbent has a higher adsorption capacity for UO22+ The reason for this experimental result is that when the pH is 3-5, the amidoxime group will be partially hydrolyzed under acidic conditions, so the adsorption capacity of UO2 2+ When the pH value is higher than 6, U(VI) is mainly in the form of UO2(OH)3 - 、UO2(CO3)3 4- and UO2(CO3)2 2- The amine oxime group is difficult to react with the amine oxime group in the form of anionic complexes. Therefore, the adsorption amount reaches the maximum value when the pH is 6. The adsorption amount of AO-NiAl-LDHs is significantly greater than that of unmodified NiAl-LDHs.
[0071] The adsorption of AO-NiAl-LDHs prepared in Example 1 on UO2 was investigated under different adsorbent qualities. 2+ The adsorption capacity (experimental conditions: adsorbent mass 3 ~ 9mg, initial uranium concentration 30mg·L -1 , pH value is 6, the volume of simulated seawater solution is 40 mL, the adsorption time is 12 h, and the reaction temperature is 298 K).
[0072] Figure 5 The effect of adsorbent mass on the adsorption amount and adsorption rate is shown. It can be seen that as the adsorbent mass increases, the adsorption amount gradually decreases, while the adsorption rate rises rapidly and then reaches a stable stage (>80%). This is because the number of active sites of the adsorbent increases with the increase in mass. When the dosage is greater than 6 mg, the adsorption rate basically reaches equilibrium, which means that the number of active sites is sufficient to accommodate the adsorbate. Taking into account both the adsorption amount and the adsorption rate, an adsorbent mass of 5 mg is determined to be the optimal value.
[0073] Application Example 2
[0074] The AO-NiAl-LDHs-1, AO-NiAl-LDHs-2 prepared in Example 2 and Example 3 and the unmodified hydrotalcite material NiAl-LDHs were subjected to UO2 2+ Adsorption comparison experiment (experimental conditions: adsorbent mass 5 mg, initial uranium concentration 30 mg·L -1 , pH value is 6, the volume of simulated seawater solution is 40 mL, the adsorption time is 12 h, and the reaction temperature is 298 K).
[0075] The adsorption capacity of unmodified NiAl-LDHs is 136.03 mg / L, that of AO-NiAl-LDHs is 178.21 mg / L, that of AO-NiAl-LDHs-1 is 170.54 mg / L, and that of AO-NiAl-LDHs-2 is 162.87 mg / L. The experimental results show that the adsorption capacity of unmodified NiAl-LDHs is lower than that of AO-NiAl-LDHs, and the adsorption performance of AO-NiAl-LDHs-2 is worse than that of AO-NiAl-LDHs and AO-NiAl-LDHs-1. The reason for this result is that the increase of amidoxime groups enhances the ability of hydrotalcite materials to adsorb uranyl ions, and the degree of oximation will also affect the adsorption capacity of the modified material. However, the oximation reagent in the reaction process should not be excessive, otherwise the purity of the product will also affect the adsorption performance.
[0076] Application Example 3
[0077] In Na + , K + Mg 2+ , Ca 2+ Under the conditions of the presence of interfering ions (experimental conditions: adsorbent mass 5 mg, initial uranium concentration 30 mg·L -1 , the interfering ion concentration is 200 mg·L -1 , pH value is 6, the volume of uranium-containing solution (not simulated seawater solution) is 40 mL, the adsorption time is 12 h, and the reaction temperature is 298 K). The AO-NiAl-LDHs prepared in Example 1 is used to adsorb UO2 in the solution. 2+ The adsorption capacity of Figure 6 shown.
[0078] The results show that AO-NiAl-LDHs has a great influence on the performance of UO2 2+ The excellent selectivity is attributed to the fact that the nitrogen-containing oxygen group in the amidoxime group can not only react with UO2 2+ It can form a coordination bond and form a stable cyclic chelate through the chelation of a large number of amidoxime groups, thereby enhancing the adsorption capacity of amidoxime groups for uranyl ions.
Claims
1. A method for preparing an amidoximated hydrotalcite material, characterized in that: The amino group is grafted onto the hydrotalcite to obtain an aminated modified hydrotalcite material; the aminated modified hydrotalcite material is grafted onto the aldehyde group to obtain an aldehyde modified hydrotalcite material; the aldehyde modified hydrotalcite material undergoes a condensation reaction with a reagent containing both an amino group and a cyanide group to obtain a cyanated modified hydrotalcite material; the cyanated modified hydrotalcite material undergoes an amidoximation reaction with an oximation reagent to obtain the obtained product.
2. The method for preparing an amidoximated hydrotalcite material according to claim 1, characterized in that: The grafted modified amino group adopts an aminosilane coupling agent; The graft modification of aldehyde groups adopts dialdehyde reagents.
3. The method for preparing an amidoximated hydrotalcite material according to claim 2, characterized in that: The general structural formula of the hydrotalcite is [M 2+ 1-x M 3+ x (OH - )2] x+ (A n- ) x / n mH2O; Among them, M 2+ With M 3+ The element ratio is (2-5):1; M 2+ Mg 2+ 、Ni 2+ or Zn 2+ ; M 3+ For Al 3+ or Fe 3+ ; A n- For CO3 2- 、NO 3- or C1 - ; The hydrotalcite has a purity of 96-99.5% and a particle size of 0.3-3 μm.
4. The method for preparing an amidoximated hydrotalcite material according to claim 2, characterized in that: The solid-liquid ratio of the hydrotalcite to the aminosilane coupling agent is (0.25-2.5) g: (1-10) mL; The reaction conditions for the graft modification of the amino group are: temperature of 40-100° C., time of 6-24 hours, and using at least one of water, ethanol, methanol, acetone, toluene, N,N-dimethylformamide, dimethyl sulfoxide and acetonitrile as solvent.
5. The method for preparing an amidoximated hydrotalcite material according to claim 4, characterized in that: The solid-liquid ratio of the amino-modified hydrotalcite material to the dialdehyde reagent is (0.5-5) g: (1-20) mL; the reaction conditions for the grafted modification of the aldehyde group are: temperature of 20-100° C., time of 2-12 h, and at least one of water, ethanol, ether, chloroform and glacial acetic acid is used as a solvent.
6. The method for preparing an amidoximated hydrotalcite material according to claim 2, characterized in that: The reagent containing both amino and cyano groups is diaminomaleonitrile or aminoacetonitrile; The mass ratio of the aldehyde-modified hydrotalcite material to the reagent containing both amino and cyano groups is (0.1-2): (0.5-4); The conditions of the condensation reaction are: temperature of 20 to 80° C. and time of 2 to 12 hours.
7. The method for preparing an amidoximated hydrotalcite material according to claim 6, characterized in that: The amidoximation reaction is to dissolve the oximation reagent, adjust the solution pH to 6-8, and then add the cyano-modified hydrotalcite material; The oximation reagent includes at least one of hydroxylamine hydrochloride, hydroxylamine sulfate and hydroxylamine phosphate; The mass ratio of the cyanation-modified hydrotalcite material to the oximation reagent is (0.1-1): (0.2-2); The conditions of the amidoximation reaction are: temperature of 60-100° C. and time of 6-24 hours.
8. An amidoximated hydrotalcite material, characterized in that: Obtained by the preparation method according to any one of claims 1 to 7.
9. The use of the amidoximated hydrotalcite material according to claim 8, characterized in that: It is used as an adsorbent for the adsorption of uranyl ions.
10. The use of an amidoximated hydrotalcite material according to claim 9, characterized in that: The adsorption conditions are as follows: pH is 3-9, and the solid-liquid ratio of the amidoximated hydrotalcite material to the uranyl ion solution is (3-12) mg:40 mL.
Citation Information
Cited By
A printing and dyeing wastewater adsorbent and a preparation method thereof
CN122702423A